Diastasis of Symphysis Pubis In 18-Years Old Female Patient Treated With Conservative Pelvic Binder: Case Report - Trisna Angga Basudana; Mifta Nurmalasari; Austana Nur Hafizh; Muhammad Hanun Mahyuddin (Journal Orthopaedi and Traumatology Surabaya, 2023)
Background: Pelvic trauma is commonly associated with high-velocity force-like road traffic accidents and carries high rates of complications, including diastasis of the symphysis pubis. The diastasis of symphysis pubis prevalence rate has been reported at 13-16%. This case report aimed to review the effectiveness of conservative pelvic binders in diastasis of the symphysis pubis in the emergency setting.Case Report: An eighteen years old female patient was referred to the Emergency Unit because of a motorcycle accident. She revealed worsening abdominal pain, unable to move both legs and swollen and bruised vulva. The patient is fully conscious, and the vital sign revealed low blood pressure of 89/56 mmHg. The AP pelvis X-ray showed diastasis symphysis pubis marked 3.87 cm wide. Immediate resuscitation was performed, stabilizing the pelvis using a conservative pelvic binder. X-ray evaluation showed surprisingly successful results as the symphyseal gap reduced to 0.66 cm. Discussion: In this case, the symphyseal gap was >2.5 cm, indicating surgical treatment. Recent studies suggest conservative therapy has good outcomes in the symphyseal gap >2.5 cm. Considering the patient's young age and no comorbidities, it was assumed that the healing process would occur quickly, so conservative treatment was chosen first. However, further evaluation is still needed due to the limitation of the follow-up from the patient. Conclusion: Conservative treatment using a pelvic binder called gurita is effective for emergencies with inadequate medical equipment.